Nutritional effects of calcium on oil palm seedling growth and suppression of Ganoderma disease - Jamaludin, Nurul Mayzaitul Azwa (2021)
Basal stem rot (BSR) disease caused by the Ganoderma species was a severe problem to the oil palm (Elaeis guineensis Jacq.) industry. Nutrients were commonly used in the fertilizers to enhance plant growth and/also to protect against abiotic and biotic stresses. Therefore, manipulation of plant nutrients, especially calcium (Ca) as an option for prevention of BSR disease in oil palm. Thus, the goals of this research were to determine the optimum concentration of Ca in oil palm seedlings, to determine the effects of different Ca sources on vegetative growth in oil palm seedlings, to assess the effects of Ca formulation treatment in the nursery to suppress Ganoderma infection in oil palm seedlings and to investigate the Ca formulation in controlling Ganoderma disease in oil palm under field condition. The optimum concentration of Ca was determined by growing of oil palm seedlings using a modified Hoagland's nutrient solution containing different concentrations of Ca for three months in a controlled environment. Concentration of 1,000 ppm of Ca from CaCl2 in the nutrient solution provided the best growth performance and development of oil palm seedlings. Subsequently, a nursery evaluation was conducted to determine the best sources of Ca and accompanying anions with oil palm seedlings planted on a Beach Ridges Interspersed with Swales (BRIS) soil for six months in MPOB nursery, Bandar Baru Bangi. An increased in seedling height, girth, chlorophyll content, and total biomass was observed on a treatment of 1,000 ppm Ca as CaSO4. Further, oil palm seedlings were pre-treated with formulated fertilizer containing 1,000 ppm Ca as CaSO4, then challenged with G. boninense PER 17 using rubber wood blocks (RWBs) sitting technique during the nursery trial (12 months) and baiting technique in the field trial (21 months). In nursery and field trials, at this concentration, the formulated fertilizer provided a better growth performance and at the same time to prevent BSR, by considerably reducing 52.8 and 81.1%, disease incidence (DI), respectively. Hence, Ca supplementation in the fertilizer could provide an alternate prevention program for BSR disease in oil palm plantation.